Fine Particle pH and its Impact on PM2.5 Control in a Megacity of Central China - Mingming Zheng; Ke Xu; Lianxin Yuan; Nan Chen; Menghua Cao (Aerosol and Air Quality Research)
Abstract Fine particle (PM2.5) acidity greatly affects the formation of secondary aerosol, and the drivers of PM2.5 pH variation are vital in understanding its effects. Moderate PM2.5 acidity was found in Wuhan, a megacity of Central China, wherein 80% of PM2.5 hold pH values ranging from 2–4. Total ammonia (NHx) and sulfate contributed 79.1–93.7% to pH changes in spring and winter, while relative humidity was the largest contributor (33.7–36.3%) in summer and fall. By sensitivity simulations, PM2.5 remained acidic with pH changes less than 0.5 units in spring, summer and fall in foreseeable future even when the concentration varied by two orders of magnitude. While pH changes in winter were three times those in the other seasons, and NHx changes was suggested as the indicator of PM2.5 pH variation in winter. Furthermore, the impact of pH on PM2.5 responses to emissions control was evaluated. The pH has opposite influences on the effect of SO2 and NOx control in reducing PM2.5, the former being more effective at low pH and the latter being more effective at high pH due to ammonium and nitrate gas-particle partitioning. The effect of NHx control on PM2.5 reduction is nonlinearly affected by pH. It is directly effective at low pH, but more ammonia control is required before achieving effectiveness at high pH. For the current particulate pH of 3–4 in Wuhan, both SO2 and NOx control are beneficial for PM2.5 reduction. However, NHx control is less effective before it is reduced by approximately 20%.